PENGHITUNGAN KEMISKINAN MULTIDIMENSI - Mokhamad Haris (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Poverty is not just economic issues, but it is a complex and multidimensional problem. Therefore, we need a multidimensional poverty indicators (covering various dimensions of life) as a complement unidimensional poverty indicator (economic dimension) that had been used officially in various countries, including Indonesia. Preparation of multidimensional poverty indicators is done by identifying the dimensions of life that was instrumental in the process of utilization of human beings in the face of poverty. The dimensions are also adjusted and should be relevant to the demands of development, both in the regional context, in line with the ideals of the national government, as well as the demands of international development (SDGs). The method used in the calculation of multidimensional poverty index is Alkire-Foster’s method.